"I feel empowered": women's perspectives on and experiences with long-acting injectable antiretroviral therapy in the USA and Spain. Issue 8 (9th August 2021) - Mantsios, Andrea; Murray, Miranda; Karver, Tahilin S.; Davis, Wendy; Margolis, David; Kumar, Princy; Swindells, Susan; Bredeek, U. Fritz; Deltoro, Miguel García; García, Rafael Rubio; Antela, Antonio; Garris, Cindy; et al.
Abstract: Long-acting injectable antiretroviral therapy has been shown to be non-inferior to daily oral antiretroviral therapy in clinical trials and may soon become part of clinical care. While most trial participants to date have been men, approximately one quarter of ongoing Phase 3 trial participants are women offering an important opportunity to understand how long-acting antiretroviral therapy is perceived and experienced by women. We conducted in-depth interviews with 80 people living with HIV participating in Phase 2 and 3 clinical trials of long-acting antiretroviral therapy in the USA and Spain. Fifteen percent (12/80) of trial participants interviewed were women. Interviews were audio-recorded, transcribed and coded using content analysis, focused on gender-specific themes. Women shared many of the positive perceptions expressed by men but also had unique perspectives, including finding that long-acting antiretroviral therapy addressed the challenge of remembering pills amidst busy day-to-day realities including multiple roles and responsibilities, is less time consuming and creates less stress compared to oral antiretroviral therapy, and is emotionally freeing and empowering. The gendered nature of women's lives shaped why and how they were satisfied with long-acting antiretroviral therapy. Findings can inform interventions and support systems to facilitate uptake of and adherence to long-acting antiretroviral therapy in women.